The Radziwill family palace in Dubingiai - Kuncevičius, Albinas; Laužikas, Rimvydas; Stankevičiūtė, Daina; Šmigelskas, Ramūnas (Archaeologia Lituana, 2010)
The initial knowledge about the representative buildings, which used to be in the Dubingiai castle place, can be traced back to the 15th c, when, in 1415 Vytautas, the grand duke of Lithuania, invited the king Jogaila to stay at Dubingiai castle place. There is no doubt that since the 15th c a stone palace stood in that place. There, as a sourcebooks claim, the queen Barbora made a stay in the middle of the 16th c. The excavated palace is dated from the end of the15th c to the beginning of the 16th c. It was a moderate building (about 17 m in the East–West direction and 15 m in the South–North direction). It was of an almost square shape, had a ground floor, first floor and a cellar, made of stone, not plastered from the outside, attributed to the gothic style. The parts which persisted and were explored during the research are: the staircase to the ground floor, a segment of the flooring of the ground floor, the ceramic tiles, and the remains of the annex (initially the watchman place, later it was transformed into the kitchen), which was projected above the cylindrical cellar arch and was of a 4 x 9 m in size (S–N x E–W direction). Above the cellars the flooring remained, it was set-up of the ceramic, non-glazed tiles (21 x 17.8 x 5.4 cm), together with that, a section of the ground floor walls, which have a thickness of a 1–1.115 m, endured. The walls were made of red bricks (27.5–30 x 13.5–14.5 x 7–8 cm), using a whitish fine-grained grout together with bulky stones, of about 0.5 x 0.6 m in size. In the middle of the 16th c, after the fall of the cellar arch in 1547, repair works were done: the old building was fortified with a counterfort sustaining the southern wall; the staircase was attributed to the guard annex on the northeastern side, it served as a separate exit to the northerly household yard; on the northeastern angle of the palace, close to the staircase, a latrin (a toilet and a leakage accumulator) was set, its shape was of a small turret, it was obviously connected to the halls of the ground and the first floor. In the beginning of the 17th c, by the initiative of Kristupas Radvila (1585–1640), the palace was reconstructed, it was enlarged in double. The evidence for the date of the annex building is the Dutch pipe piece, which was found in the base pit close to the Southern wall. It has a repousse inscription on its stem, it says “IONAS” (letters N and S written backwards), and 1633. The length of the new annex – 11.5 m (E–W direction), the width – about 10.5 m2. Accordingly, the area of the western lodgments (hall and a hallway) took 38.4 m and 17.9 m2, while the second hall and the hallway, which were attached to the old palace, took 18.5 m2 and 7.5 m2. The outer walls of the annex were 0,75–0,85 m in thickness. They were tied in renaissance way with the 28 x 14 x 7 cm bricks with passes. Comparatively thin outer walls of the building show, that the annex had only one floor. The annex floor was reveted with square, ceramic, non-glazed tiles, their measurements are 27.5 x 27.5 x 5 cm. The lodgements had stained glass windows, as they are mentioned in the stock. During the researches quite a lot of greenish glass (0.2 cm in thickness) was found, most of the lightplates had a shape of a triangle. The inner hall walls of (0.5 m high persisted) were plastered with white daub. It is possible that the ceiling was wooden, the roof was covered with flat tilings (a were found in the remains of the palace). One of the most interesting elements of the palace interior is the place of a former tile stove, it was detected in the annex hall. During the research the bakestone of the stove was found, it was of a 1.62 m length, the legs of the bakestone persisted very well. They are circular, 14 cm in diameter, 7 cm in high, the bricks were made in a round shape reminding columns. Among the palace findings there are a lot of building materials: bricks and brickbats, calcimine, flat tiling, more seldom pantiles, fragments of stained-glass and frames. Another large part of findings consists of tiles and kitchen-ceramics. Traditional techniques such as modeling and throwing prevail, it points to the rough moulding, grinded stone, usage of wide clay straps, the articles were burned in oxidation. Some articles were decorated using the round stamp ornament. Very few fragments of gothic or black – urban ceramics were found: the bottom parts of a bowl, decorated with a round stamp ornament, and a thin-pane jar. The tiles were undamaged and very different: concave, cylindrical and square tiles; decorated with the vegetal ornaments and blazonry; backgrounds differ in colour, some of them white, some blue, or green. In the middle of the tile there is an armorial brown eagle with yellow legs, a shield. The green-glazed tiles were decorated with the initials of Žygimantas Augustas, the armorial tile, with Vytis, the square tiles decorated with religious ornaments (Madonna and a pear). The tiles of the 17th c were decorated with vegetal ornaments and covered with a green glaze, or were not glazed at all. Other findings were: segments of chalices, a knife, an ax, a ring, a fingertip, the bottom part of a glass mug, the sole of a wineglass, stylus (medieval tool for writing), a chess counter made of bone, a tip of a bow arrow, a stone spindle, bone planking ornamented with geometrical motives, coins (a coin of Kazimieras Jogailaitis (3rd type), Aleksandras half-penny, half-pennies of Žygimantas Augustas, shilling of Karolis the XIth, half-penny of Žygimantas the Old, Jonas Kazimeras shillings etc). The research of Dubingiai palace will continue. It is foreseen to investigate the gothic cellars and the yard of the palace. The excavated masonry were registered in detail, all the cultural layers were fixed with the 3D scanner. A detailed photofixation was made, the course of the research is being filmed, the initial stylistical cartogram of the masonry is already prepared, about 10 000 archaeological findings are already inventorized. The excavated parts of the palace are covered with a temporal mantle and partly mothballed, but in the short run a special, modern museum-like mantle is going to be built. The author of the mantle project is an architect R. Zilinskas.